SOS Cuidador - aplicativo para auxiliar as demandas educativas do cuidador familiar - Belo, Andressa da Silva Costa (2018)
In recent years, there has been a significant increase in the elderly population. This phenomenon, demographic transition, in which the birth and death rates have progressively decreased, is accompanied by the increase in the number of chronic non-communicable diseases, consequent increase in medication intake and elderly dependents. Due to the high cost, this care is usually taken care of by family caregivers who are not prepared to play this role and the complexities demanded by it. After the systematic analysis of existing caregivers applications, the SOS Cuidador application was developed through the general process methodology for software engineering, which gathers information on personal data, medication, procedures, food and important contacts to assist in care of the dependent elderly. To analyze the usability of the SOS Caregiver application, the Usability Test was carried out to identify the percentage of correct answers by activities and the users' perception about the interface, ease of use and usefulness of the application to help the daily activities of the family caregiver. All activities proposed in the application had great success percentages, being one hundred percent in the activities of Caregiver Registration, Login, New Patient Registration, Open Editing Screen, Edit Information in the Patient File and Log Out. The perception of the users of the SOS Caregiver application was satisfactory, with the highest index being the Utility category. It is concluded that the SOS Cuidador application is an easy-to-use application when you have daily experience with the use of mobile applications and was satisfactorily perceived by users as a technology that would aid in the daily activities of the caregiver, ie the SOS Caregiver application can be considered as part of the solutions for an aging population with more quality.